Amino acids and their transporters in T cell immunity and cancer therapy - Wang, Weimin (Mol Cell, 2020)
Metabolism reprogramming is critical for both cancer progression and effective immune responses in the tumor microenvironment. Amino acid metabolism in different cells and their cross-talk shape tumor immunity and therapy efficacy in patients with cancer. In this review, we focus on multiple amino acids and their transporters, solute carriers (SLCs) members. We discuss their involvement in the regulation of the immune responses in the tumor microenvironment, and assess their associations with cancer immunotherapy, chemotherapy, and radiation therapy; as well as review their potential as targets for cancer therapy. We stress the necessity to understand individual amino acids and their transporters in different cell subsets, the molecular intersection between amino acid metabolism, and effective T cell immunity and its relevance in cancer therapies.